MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA SMP MELALUI PENDEKATAN SAINTIFIK BERBASIS ETNOMATEMATIKA - Ratna Sariningsih; Gida Kadarisma (Jurnal Ilmiah P2M STKIP Siliwangi, 2016)
This research is motivated by the lack of ability to think creatively Mathematically junior secondary students. This research aims to determine differences in achievement and increase the ability of creative thinking and independent learning as well as the association between mathematics student who obtained the usual scientific approach to obtaining scientific approach based etnomatematika. This research method is experimental design with pretest posttest control group design in this study population eighth grade students in one of the Junior High School in Bandung, the sample was taken two classes of ninth grade there. Instruments in this study is a test description of critical and creative thinking skills as much as 5 mathematical problems. Based on the results of the study are Differences in Achievement and improvement Ability Creative Thinking Mathematically junior high school students are learning to use PendekatanSaintifik usual with the use Approach Scientific based etnomatematika, and there is no difference Independence Learning student learning using the approach Scientific with the gain approaches saintif based Etnomatematika and are associated antarakemampuan Creative Thinking Mathematically students with learning independence student learning using etnomatematika-based Scientific Approach.